2014
DOI: 10.1515/cclm-2014-0265
|View full text |Cite
|
Sign up to set email alerts
|

Structural myocardial alterations in diabetes and hypertension: the role of galectin-3

Abstract: This study revealed that levels of galectin-3 were higher in patients with both T2D and HT, and correlated with LV mass, indicating the potential role of this biomarker for early detection of myocardial structural and functional alterations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 6 publications
4
13
0
Order By: Relevance
“…In another study carried out with diabetic and hypertensive patients, galectin levels were detected to be higher among hypertensive patients compared with normotensives and were determined to be associated with myocardial fibrosis, which was evaluated with late gadolinium enhancement [34]. Similarly, in our study, galectin-3 levels were found to be strongly correlated with LMVI among hypertensive patients as well.…”
Section: Discussionsupporting
confidence: 81%
“…In another study carried out with diabetic and hypertensive patients, galectin levels were detected to be higher among hypertensive patients compared with normotensives and were determined to be associated with myocardial fibrosis, which was evaluated with late gadolinium enhancement [34]. Similarly, in our study, galectin-3 levels were found to be strongly correlated with LMVI among hypertensive patients as well.…”
Section: Discussionsupporting
confidence: 81%
“…In this study, higher levels of Gal-3 are associated with the development of type 2 DM. The obtained results substantiate the study of Seferovic et al, [28] which describes elevated levels of Gal-3 in patients with type 2 DM that were strongly correlated with HbA1c levels. Yilmaz et al [29] showed that Gal-3 may be an independent predictor of type 2 DM in general.…”
Section: [27]supporting
confidence: 91%
“…In clinical studies, circulating galectin-3 was higher in type 2 DM patients [71][72][73][74] and thought to be a risk factor for vascular complications, such as heart failure, nephropathy, peripheral artery disease, and other vascular complications. 71 Patients with galectin-3 level 25 ng/mL exhibited a 11.4-fold higher risk of microvascular complications (retinopathy and/or nephropathy) and a 8.5-fold increased risk of macrovascular complications (myocardial infraction, angina pectoris, cerebrovascular event, and peripheral artery disease) compared to patients with galectin-3 level 10 ng/mL.…”
Section: Galectin-3 In Metabolic Disease Pathogenesismentioning
confidence: 99%